Respiratory Neuropathy as an Important Component of Critical Illness Polyneuromyopathy - R. T. Rakhimov; I. N. Leyderman; A. A. Belkin (Неотложная медицинская помощь, 2020)
ABSTRACT. The attention of neurologists, neurosurgeons, intensive care physicians has been attracted recently by the new PICS (Post Intensive Care Syndrome) symptom complex (PIC) or PIC syndrome — Post Intensive Care Syndrome. One of the most severe options for PIT syndrome is critical illness polymyoneuropathy (CIP). Polyneuropathy (Critical illness polyneuropathies, or CIP) and myopathy (Critical illness myopathies, or CIM) are common complications of critical care. Several syndromes of muscle weakness are combined under the term «Intensive care unit-acquired weakness» or ICUAW. Respiratory neuropathy is a special case of PMCS, where respiratory failure is associated with damage to the neuromuscular apparatus of external respiration. The clinical consequence of respiratory neuropathy is an unsuccessful weaning from ventilator and a long stay of patients in ICU. This systematic review of the literature is an analysis of publications devoted to the main pathogenetic mechanisms of the development of CIP and respiratory neuropathy, diagnostic methods, new therapeutic approaches to the treatment of ICU patients with respiratory neuropathy. The special attention is given to the problem of acute muscle wasting, diagnosis and correction of proteinenergy metabolism disorders in patients with respiratory neuropathy.